Zmieniając siebie, zmieniam też swoją szkołę. Rzecz o wspólnym trwaniu i działaniu w Stowarzyszeniu Szkół Innowacyjnych Regionu Opolskiego = By changing myself, i also change my school. On staying and working together in the Opole Region Innovative Schools Association - Koszyk, Irena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to present the grassroots innovation movement in public schools, to show selected activities undertaken by Regional Associations and the form of their dissemination using the example of the Opole Region Innovative Schools Association. The author describes the schools` undertakings and presents sources of inspiration, directions and methods of work in associated schools, proving that by changing ourselves, we also change our school.
Keywords: innovation; creativity; cooperation; inspiration; decentralisation; dissemination; innowacja; twórczość; współpraca; inspiracja; decentralizacja; upowszechnienie